Analisis Studi Komparasi Kebijakan Pendidikan Dasar di Jepang dan Finlandia - Putri, Ilhami Cahaya; Tunnur, Melati Aulia; Mardatillah, Aulia Mardatillah; Ananda, Rizki Ananda; Witarsa, Ramdhan Witarsa (Universitas Negeri Makassar, 2023)
This study aims to describe a comparative study of basic education policies in Japan and Finland. This research method uses qualitative research methods with a literature review approach. The research stages were carried out starting from article collection, article reduction, article display, discussion, and conclusion. Sources of research data are articles from accredited national journals and articles from accredited international journals in the last 6 years (2017-2022). The results showed that from 21 articles, 3 articles were obtained that matched the topic title. Comparative studies of basic education policies in Japan and Finland of course have different factors, for example, Japan is successful in its education by prioritizing character education as its main goal, Finland is successful by prioritizing factors related to study time, facilities, and teachers. Some of the factors that made Japan and Finland advanced in education can be adapted from these factors in Indonesia so that the quality of basic education can improve.